2019
DOI: 10.1556/2006.8.2019.73
|View full text |Cite
|
Sign up to set email alerts
|

Similar roles for recovery capital but not stress in women and men recovering from gambling disorder

Abstract: Background Understanding gender-related differences is important in recovery processes. Previous studies have investigated gender-related differences in factors associated with gambling disorder (GD), but none to date have considered both positive and negative resources related to recovery. Using a recovery capital (RC) framework that considers multiple resources available during recovery, this study examined gender-related similarities and differences in associations between positive resources (RC, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…The increase in the incidence and prevalence of behavioral addictions and the relevance of early initiation of the problem of gambling disorder and compulsive buying, together with their serious consequences, make it necessary to better understand these problems in young people and adolescents in order to develop and adapt prevention and treatment programs to specific needs according to gender and age. Furthermore, the understanding of gender-related differences is of great importance in the treatment of behavioral addictions [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the incidence and prevalence of behavioral addictions and the relevance of early initiation of the problem of gambling disorder and compulsive buying, together with their serious consequences, make it necessary to better understand these problems in young people and adolescents in order to develop and adapt prevention and treatment programs to specific needs according to gender and age. Furthermore, the understanding of gender-related differences is of great importance in the treatment of behavioral addictions [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to a current meta-analysis, the prevalence of gambling disorder is estimated to be 1.29% in adults (Gabellini et al, 2023 ).Concerning GD prevalence as a function of sex, a ratio of 2:8 of women and men has been found (Merkouris et al, 2016 ). Although there is still limited gender-specific literature on GD, studies have reported sex-related differences in terms of psychopathological profile, gambling behaviour patterns, associated consequences or pathogenesis of GD (Gavriel-Fried et al, 2019 ; Jiménez-Murcia et al, 2020 ; Macía et al, 2023 ). In this regard, for example, it has been observed that different emotions are involved in women and men with gambling problems.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, these studies actually used the definition of "sustained remission"; that is, after the full criteria for GD had previously been met, none of the criteria for GD were met during a period of 12 months or longer (Bischof et al, 2020;Gavriel-Fried, Moretta, & Potenza, 2020b;Rossini-Dib, Fuentes, & Tavares, 2015;Slutske, 2006;Slutske, Blaszczynski, & Martin, 2009. Similarly, Gavriel-Fried et al used the notion of "improvement in GD symptoms" by subtracting the number of DSM-5 diagnostic criteria pertaining to GD that were met during the past year from the number of criteria met over the focal individual's lifetime (Gavriel-Fried, Moretta, & Potenza, 2019, 2020a, 2020c.…”
Section: Recovery As Abstinencementioning
confidence: 99%